Antimicrobial Resistance of Non-Typhoid Salmonella in Meat and Meat Products - Sandra M. Rincón-Gamboa; Raúl A. Poutou-Piñales; Ana K. Carrascal-Camacho (Foods, 2021)
Salmonella enterica serovars are associated with numerous annual deaths worldwide and are responsible for a large number of foodborne diseases. Within this frame of reference, knowledge of antimicrobial susceptibility represents the fundamental approach of most Salmonella treatments. Therefore, scientific publications of antimicrobial susceptibilities and resistance must be precise, with interpretations adjusted to a particular standard. Hence, the three objectives in this study were: (i) to describe the frequency of antimicrobial-resistant isolates of Non-Typhoidal Salmonella (NTS) isolated from beef, pork, chicken meat, and other meat products; (ii) to describe the distribution of serovars and their multi-resistance to antibiotics for clinical use (veterinary and human) between 1996 and 2019; and (iii) to propose additional considerations that could improve the use and usefulness of the published results. Our results determined that the predominant isolates came from poultry. Enteritidis and Typhimurium were the most reported serovars by MIC (with both having the highest resistance to TET) while the lowest resistance was to CIP and CRO for Enteritidis and Typhimurium, respectively. The multi-resistance pattern AMP AMC CEP GEN KAN STR TET was the most frequently observed pattern by MIC in Montevideo and Seftenberg, while, for disc diffusion, the pattern AMP STR TET was the most frequent in the Bredeney serotype. In conclusion, researchers should carry out homogeneous sampling procedures, identify the types of the samples, use standard identification methods, and employ appropriate standards for antimicrobial susceptibility interpretation. Additionally, there is also a need for all WHO members to comply with the WHA 73.5 resolution. Our final recommendation is for all producers to reduce antibiotic prophylactic use.